Whose interest does it serve? A confucian community engagement - Khanyile, M. (South African Journal of Higher Education, 2020)
It is incontestable that universities assumed the so-called “third mission” which means that they include community engagement in their activities in order to be financially viable. This paradigm shift begs the question: In terms of whose interest does community engagement serve? It has been difficult to separate community engagement from traditional research as community engagement projects can emerge from new research ideas. As an emerging property, community engagement should be holistic rather than reductionist, in order to afford universities opportunities to function as sites of citizenship, as well as to contribute to the knowledge society and knowledge economy, and generate mutual benefits. However, there are no instruments used to gauge the benefits for communities, while the benefits for academics and universities are outputs, promotions and revenue. The epistemologies and methodologies used in community engagement activities are often foreign to the communities and neither appreciate nor understand their problems. Instead of universities being communities of scholars, they have become workplaces. The communities are often pawns and objects in the hidden agendas of researchers and institutions. Some of these agendas include but are not limited to, university entrepreneurialism, dispossession of indigenous knowledge of local communities, advancement of commercialisation and capitalism, and meeting academic key performance areas to be eligible for promotion. This conceptual article argues that community engagement is a complex phenomenon that requires a systemic non-linear approach.